THE IMPROVEMENT OF STUDENT’S STUDY INTEREST AND MASTERY OF CONCEPT IN THE BASIC LAWS OF CHEMISTRY MATERY BY THE LEARNING CYCLE 3E (LC 3E) LEARNING MODEL - rahmanudin rahmanudin; ratu betta rudibyani; tasviri efkar (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
This study aims to obtain an effective instructional model increase interest  and mastery of the concept of class XI science in chemical equilibrium material. The population in this study were all students of class XI Science SMAN 12 Bandar Lampung Year 2012-2013 semester with class XI IPA 4 as class Science and XI 5 as a sample. This research method is a quasi-experimental pretest posttest control group design. Learning effectiveness is measured by comparing the difference in value to the difference between pretest and posttest maximum value with the value of the pretest. The results showed the average value of the index gain interest in the control and experimental classes respectively 0,22 and 0,34; and the mean index gain mastery of concepts for the control and experimental classes respectively 0,33 and 0,55. Based on hypothesis testing, it was concluded that learning through the class with LC 3E has an interest and mastery of concepts that is higher than learning conventional class. This suggests that the learning material through chemical equilibrium LC 3E learning is more effective in increasing students' interest and mastery of concepts. Keywords: Learning Cycle 3E (LC3E), study interest, and mastery of concept